Iraqi Legal System of International Environmental Responsibility - Reyam Naji Ajmi (Journal of Global Pharma Technology, 2019)
The domestic legal systems have shown an interest that varies from one system to another in the environment in which man lives. In the pursuit of progress and advancement, man has achieved great success in various fields, but on the other hand, he has contributed intentionally and unintentionally to harm the environment in which he lives, and the reaction of States when recognizing the dangers posed to the environment in an initiative to work to support their domestic laws to The adoption of programs and plans for the protection and preservation of the environment within the limits of its regional competence and the development of some laws and regulations in the field of the environment, which led to the flourishing support for domestic law in many countries, especially the developed world in the field of the environment, which led to the emergence of a series of national legislation However, efforts to protect and preserve the environment at the domestic level cannot lead to achieving their goals unless they are coupled with efforts at the other level, namely international relations, because the field of the environment highlights the close link between domestic and international law. The environment for natural and geographical considerations is ultimately only one integrated and connected in a natural format.Keywords: Environmental Law, Pollution.